NanoNet: Rapid and accurate end-to-end nanobody modeling by deep learning - Cohen, Tomer; Halfon, Matan; Schneidman-Duhovny, Dina (Frontiers in Immunology, 2022)
Antibodies are a rapidly growing class of therapeutics. Recently, single domain camelid VHH antibodies, and their recognition nanobody domain (Nb) appeared as a cost-effective highly stable alternative to full-length antibodies. There is a growing need for high-throughput epitope mapping based on accurate structural modeling of the variable domains that share a common fold and differ in the Complementarity Determining Regions (CDRs). We develop a deep learning end-to-end model, NanoNet, that given a sequence directly produces the 3D coordinates of the backbone and Cβ atoms of the entire VH domain. For the Nb test set, NanoNet achieves 3.16 ̊A average RMSD for the most variable CDR3 loops and 2.65 ̊A 1.73 ̊A for the CDR1, CDR2 loops respectively. The accuracy for antibody VH domains is even higher: 2.38 ̊A RMSD for CDR3 and 0.885 ̊A 0.955 ̊A for the CDR1, CDR2 loops respectively. NanoNet run times allow generation of ∼1M nanobody structures in less than 4 hours on a standard CPU computer enabling high-throughput structure modeling. NanoNet is available at GitHub: https://github.com/dina-lab3D/NanoNet